Symmetry torques muscles responsible for the rotation of the spine in judo - Walowski, K.; Poliszczuk, D. (Journal of Combat Sports and Martial Arts, 2014)
Due to the limited number of publications and reports on strength of the muscles responsible for trunk rotation and the growing interest in the problem of symmetry in sport, an attempt was made to determine torque symmetry in muscles responsible for trunk rotation. The aim of the study was to recognize asymmetries in the torque of muscles responsible for trunk rotation and handgrip in Polish National Judo Team. Material and methods. The sample comprised the members of the Polish National Judo Team. The study group included 16 males participating in the meeting at the Centre of Olympic Training in Zakopane. The applied approach involved measurements of torque developed during trunk rotation under static conditions and handgrip strength. Devices specially constructed for this purpose were used for the measurements. Statistical analysis was conducted using ANOVA test. The measurements also included handgrip strength in the right and left arm using an electric dynamometer. Results. The analysis of the collected material showed no differences in torque values in muscles responsible for spinal right-sided and left-sided rotation, and in handgrip strength between the right and the left arm. Conclusions. In the studied sample no apparent asymmetry of torque was observed in the muscles responsible for trunk rotation and handgrip strength. Balancing the strength of muscles responsible for trunk rotation can undoubtedly extend the opportunities for using tactical skills by the competitors. The higher the competitors level of training, the lower the differences are in torque of muscles responsible for handgrip strength.